2017
DOI: 10.12659/msm.904318
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine Profile in Patients with Type 2 Diabetes Depends on Degree of Obesity

Abstract: BackgroundThe fast pace of life, promoting fast food consumption and low physical activity, has resulted in obesity and/or diabetes as being serious social problems.The aim of the present study was to evaluate concentrations of selected adipokines (leptin, adiponectin, resistin, and visfatin) and to assess the leptin/adiponectin ratio in plasma of type 2 diabetes (T2D) patients in relation to degree of obesity.Material/MethodsThe study comprised 92 T2D subjects divided into 4 groups according to BMI value – I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
(59 reference statements)
2
28
0
1
Order By: Relevance
“…The magnitude of the influence of adiposity on other adipokines in MetS and subsequent T2DM also varies in the literature. Comparison of normal weight, overweight, obese and morbidly obese T2DM patients with metabolically healthy normal weight controls showed a difference in adipokine markers that did not exist in normal weight T2DM subjects, but the difference was exacerbated by being overweight or (morbidly) obese (49). Adiponectin, a commonly measured anti-inflammatory adipokine, has been shown to be lower in obese subjects compared to metabolically healthy normal weight controls, but there was no difference between obese subjects and T2DM patients (50).…”
Section: Discussionmentioning
confidence: 92%
“…The magnitude of the influence of adiposity on other adipokines in MetS and subsequent T2DM also varies in the literature. Comparison of normal weight, overweight, obese and morbidly obese T2DM patients with metabolically healthy normal weight controls showed a difference in adipokine markers that did not exist in normal weight T2DM subjects, but the difference was exacerbated by being overweight or (morbidly) obese (49). Adiponectin, a commonly measured anti-inflammatory adipokine, has been shown to be lower in obese subjects compared to metabolically healthy normal weight controls, but there was no difference between obese subjects and T2DM patients (50).…”
Section: Discussionmentioning
confidence: 92%
“…The finding of this study, that a functional analysis of the subnetworks encompassing HOMA-β-associated GWAS signal-harboring genes enriched pathways of especially fat metabolism, with a central role of adipose tissues, support the "lipotoxicity" theory of beta cell failure in T2D, where heightened free fatty acid flux results from adipose tissue leads to increased insulin resistance. Indeed, several studies have demonstrated that obese type 2 diabetic patients presented a disturbed adipokine profile, which seems to be an important link between adiposity (i.e., insulin resistance), beta cell dysfunction, and T2D [29,30]. There is pharmacological evidence that drugs like insulin and thiazolidinediones significantly suppress the free fatty acid flux and improves beta cell functions in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…также показали достоверные различия уровней резистина у пациентов с ожирением и здоровых людей, однако значимую связь резистина с гликемией натощак и другими метаболическими показателями им удалось выявить только у здоровых лиц [18]. Другие авторы также не выявили корреляции уровня резистина ни с ИМТ у больных с избыточной массой тела [19,20], ни с наличием СД 2 типа [21].…”
Section: Discussionunclassified